STUDY ON THE REPRESENTATION OF THE PLÜCKER CONOID - DRAGAN Delia; BĂRBÎNŢĂ Dorin (Journal of Industrial Design and Engineering Graphics, 2008)
The architecture and construction related design requires an in-depth knowledge of all the systems of representation of solids and surfaces. This paper presents a comparative study on the representation of the Plücker conoid using the three systems of representation, i.e. axonometry, the orthogonal projection on two planes of projection and the projection with elevation. Each of these representation systems has its own advantages and disadvantages. They relate to the practical aspect of measuring the true lengths, respectively sizes of angles and surfaces. Then, the way in which the representation is perceived spatially by specialists or non-specialists is also of importance.